Travel in London. Report 13. - (:unkn) unknown (My University, 2020)
Travel in London is TfL’s annual publication that summarises trends and developments relating to travel and transport in London. Its principal function is to describe how travel is changing and to provide an interpretative overview of progress towards implementing the Mayor’s Transport Strategy. It also provides an evidence and analysis base for the general use of stakeholders and policymakers. The first part of the report reviews trends and developments in the pre-pandemic period up to the end of 2019 or the 2019/20 financial year, primarily in terms of the aims of the Mayor’s Transport Strategy. The second part of the report considers developments related to the pandemic in 2020, in so far as available data allow, and recognising that at the time of writing the pandemic is still playing out. The aim is to assemble and interpret an emerging evidence base that can be used to guide the recovery and inform the longer-term plans for supporting growth, prosperity and daily life in London over the next decade or so.
Keywords: Großstadt; Stadtverkehrsplanung; Verkehrsentwicklung; Krisensituation; Corona-Krise